2014
DOI: 10.1186/1757-2215-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity edema in patients with early ovarian cancer

Abstract: BackgroundThe objective of this study was to investigate clinical manifestations of lower extremity edema (LEE) in early ovarian cancer.MethodsPatients with early ovarian cancer who underwent staging surgery between January 2001 and December 2010. Medical records for LEE and/or responses to the Gynecologic Cancer Lymphedema Questionnaire (GCLQ) were evaluated.ResultsPatients had a median age of 46 years. Twenty-nine patients (40.8%) had past (13 patients, 44.8%) and/or current patient-reported LEE (16 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…Recently, Beesley et al reported that 13% of patients treated with endometrial cancer experienced LLL [6]. Our previous study also showed that even in early-stage ovarian cancer cases, about four of every 10 patients reported past and/or current lower extremity edema and related symptoms after surgical staging including pelvic LND [7].…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Beesley et al reported that 13% of patients treated with endometrial cancer experienced LLL [6]. Our previous study also showed that even in early-stage ovarian cancer cases, about four of every 10 patients reported past and/or current lower extremity edema and related symptoms after surgical staging including pelvic LND [7].…”
Section: Introductionmentioning
confidence: 92%
“…Again, lymphadenectomy is the most important prognostic factor 38 39. In ovarian cancer, surgical evaluation of the pelvic nodes and para-aortics up to the renal vessels is considered the standard of care for early-stage disease confined to the ovary and/or pelvis 40. Lim et al examined a cohort of ovarian cancer patients with early-stage disease, 97.2% of whom underwent lymphadenectomy, and reported that 55% had lymphedema.…”
Section: Secondary Lymphedema In Gynecologic Malignanciesmentioning
confidence: 99%
“…Lim et al examined a cohort of ovarian cancer patients with early-stage disease, 97.2% of whom underwent lymphadenectomy, and reported that 55% had lymphedema. It should be noted that 57.4% had greater than 35 lymph nodes excised 40. The majority of patients with newly diagnosed ovarian cancer actually present with advanced stage disease, in which case such a systematic lymphadenectomy is not routinely performed except in the setting of grossly enlarged nodes 41…”
Section: Secondary Lymphedema In Gynecologic Malignanciesmentioning
confidence: 99%
“…The reported incidence of LLL among OC patients ranges from 4.7% to 40.8% (13,56) and most of the studies were performed on heterogeneous cohorts including also patients with CC and EC (1,13,14,34,39,40). Only one study specifically addressed OC patients by means of subjective evaluation (56), reporting an incidence of 40.8% (past 18.3% and current 22.5%); LLL developed in most of the cases (86.2%) in the first year after surgery and persisted more than 6 months after treatment in 62.1% of the women.…”
Section: Incidencementioning
confidence: 99%